The Enhancement of Student’s Communication Skills through Remap-NHT in Learning Biology - Fiqih Zahra; Siti Zubaidah; Susriyati Mahanal (Jurnal Pendidikan Sains, 2020)
Abstract: Empowering communication skills can be done through the implementation of appropriate learning models. Remap-NHT could potentially improve communication skills through the syntax of reading, concept mapping, and discussion. This study aims to determine the influence of Remap-NHT on communication skills conducted in August-December 2019. Samples amounted are 100 students from three classes of XI MIPA SMA Negeri 4 Malang, each of which has been discussed with Remap-NHT, NHT, and control. Data were analyzed using Oneway-Ancova, which previously carried out the One-Sample Kolmogorov-Smirnov test and Levene’s Test of Equality of Error Variances. The results showed that Remap-NHT significantly improved communication skills compared to NHT and control.Key Words: communication skills; remap-NHTAbstrak: Pemberdayaan keterampilan komunikasi dapat dilakukan melalui penerapan model pembelajaran yang sesuai. Model pembelajaran Remap-NHT berpotensi meningkatkan keterampilan komunikasi melalui sintaks membaca, membuat peta konsep, dan diskusi. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Remap-NHT terhadap keterampilan komunikasi yang dilakukan pada bulan Agustus-Desember 2019. Sampel berjumlah 100 siswa dari tiga kelas XI MIPA SMA Negeri 4 Malang yang masing-masing dibelajarkan dengan Remap-NHT, NHT, dan kontrol. Data dianalisis menggunakan Oneway-Ancova yang sebelumnya dilakukan uji prasyarat One-Sample Kolmogorov-Smirnov test dan Levene’s Test of Equality of Error Variances. Hasil penelitian menunjukkan bahwa Remap-NHT lebih signifikan meningkatkan keterampilan komunikasi dibandingkan dengan NHT dan kontrol.Kata kunci: kemampuan komunikasi; remap-NHT